Analisis Pengaruh Penambahan Abu Tempurung Kelapa Terhadap Kuat Tekan Beton Geopolimer Dengan dan Tanpa Zat Tambah - Sikanna, Ferdi; Setiawan, Arman; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
This study aims to determine how the effect of adding coconut shell ash as a partial substitute for fly ash on the compressive strength of geopolymer concrete and the effect of adding and without adding additives to variations of coconut shell ash. The method of this research is to compare the control concrete with the variation of fly ash mixed with coconut shell ash 5%, 10%, 15%, with and without the addition of 2% superplastizer. From the results of this study it can be concluded that the concrete using 5% coconut shell ash increased by 3.7% from the control concrete, and at the addition of 10% and 15% coconut shell ash decreased the compressive strength of the concrete by 36% and 47, respectively. 5%. For the comparison of the addition of 2% superplastizer to the compressive strength of coconut shell ash geopolymer concrete without using additives of 7.8%, 23.4% and 16.8%, from each variation of coconut shell ash.